Autoimmune-polyendocrinopathy-candidiasis-ectodermal-dystrophy in Calabria: clinical, immunological and genetic patterns. - Betterle, C; Ghizzoni, L; Cassio, A; Baronio, F; Cervato, S; Garelli, S; Barbi, E; Tonini, G (J Endocrinol Invest, 2012)
UNLABELLED: Autoimmune polyendocrinopathy-candidiasis-ectodermal- dystrophy (APECED), also known as autoimmune polyendocrine syndrome type 1 (APS-1), is a very rare disease. Diagnosis requires the presence of at least two of three major clinical features: chronic mucocutaneous candidiasis, chronic hypoparathyroidism, and Addison's disease. DESIGN: In this study, we analyzed Autoimmune Regulator (AIRE) gene mutations and genotype-phenotype correlation in APECED patients originating from Calabria, a region in the south of Italy. PATIENTS AND METHODS: Four patients and their first-degree relatives were evaluated for clinical manifestations, autoantibody presence and AIRE gene mutations. RESULTS: Three patients carried a homozygous W78R mutation on exon 2, typical of patients with APECED from Apulia; the fourth patient had a homozygous R203X mutation on exon 5, typical of APECED patients from Sicily. Clinical disease expression showed wide variability. Analysis of relatives allowed the identification of 6 heterozygotes, none of whom showed major findings of APECED. CONCLUSIONS: No AIRE gene mutations specific to Calabria were found in patients with APS-1, but mutations similar to those in patients from Apulia and Sicily. Heterozygosity for AIRE gene mutation is not associated with major findings of APECED.
Keywords: Adolescent; Adult; Autoantibodies; Child; Female; Genetic Association Studies; Heterozygote; Homozygote; Humans; Italy; Male; Mutation; Polyendocrinopathies, Autoimmune; Prognosis; Sicily; Transcription Factors; Young Adult